Altered colonic microflora and its metabolic profile in mice with acute viral myocarditis induced by coxsackievirus B3 - Yimin Xue; Shirong Lin; Mingguang Chen; Jun Ke; Jiuyun Zhang; Qiaolian Fan; Yimei Chen; Feng Chen (Virology Journal, 2024)
Abstract Mounting evidence suggests that the gut-heart axis is critical in the pathogenesis of cardiovascular diseases. The gut serves as the primary pathway through which Coxsackievirus B3 (CVB3) infects its host, leading to acute viral myocarditis (AVMC). However, little is known about the role of gut microflora and its metabolites in the development of AVMC. The AVMC model was established by intraperitoneal injection of CVB3 in mice. Then, 16S ribosomal RNA (16S rRNA) gene sequencing and ultra-high-performance liquid chromatography-tandem mass spectrometry (UHPLC-MS/MS) untargeted metabolomics profiling were performed to analyze the microflora composition and metabolic profile of colonic contents. Compared to the Control mice, the AVMC mice displayed a significant reduction in gut microflora richness and diversity, as revealed by an increased abundance of Proteobacteria and a decreased abundance of Cyanobacteria and Desulfobacterota. LEfSe analysis indicated that the main genera differing between the two groups were Escherichia-Shigella, Lactobacillus, Clostridium_sensu_stricto_1, Prevotellaceae_UCG-001, and Odoribacter. Based on the criterion of OPLS-DA VIP ≥ 1.0 and p-value < 0.05, a total of 198 differential metabolites (DMs) were identified in the gut, including 79 upregulated and 119 downregulated metabolites, of which lipids and lipid-like molecules accounted for the largest proportion. Notably, both altered gut bacterial taxa and metabolites were significantly enriched in the Lipid metabolism pathway, with Traumatic acid (TA), Alpha-Linolenic acid (ALA), Eicosapentaenoic acid (EPA), and Docosahexaenoic acid (DHA) being the key DMs in the pathway. Additionally, significant positive correlations (|r| > 0.80 and p < 0.05) were found between TA levels and Anaerotruncus and Bilophila abundance, between EPA levels and Clostridium_sensu_stricto_1 abundance, and between DHA levels and Escherichia-Shigella abundance, respectively. CVB3 infection leads to notable alterations in gut microflora composition and its metabolic profile, which may participate in AVMC development. Our findings provide important clues for future in-depth studies on AVMC etiology.